ISAR Imaging of Rotating Target with Equal Changing Acceleration Based on the Cubic Phase Function. (12th March 2008) - Wang Wang, Yong Yong; Jiang Jiang, Yi-cheng Yi-cheng
Abstract : When reconstructing the ISAR image of a maneuvering target rotating approximately with the equal changing acceleration, the received signals can be considered as the multicomponent cubic phase signals. If the model of rotating with constant acceleration is used here, the errors of the reconstructed images cannot be neglected, and a lot of pseudo scatterers are produced. Hence, the ISAR imaging of rotating target with equal changing acceleration based on the cubic phase (CP) function is presented in this paper. The CP function is applied to estimate the parameters of the multicomponent cubic phase signals, and the clear instantaneous ISAR images are obtained. The results of simulated data demonstrate the effectiveness of the method proposed.